2009
DOI: 10.1177/0022427809348905
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Co-Offending Network Redundancy and Offending Versatility

Abstract: The role of criminal, social interactions occupies a central place in criminology, yet minimal research exists on the relationship between co-offender networks and dimensions of offending. Drawing on the social network literature, this investigation hypothesizes that a link exists between the level of redundancy (i.e., the extent of overlap) in an individual’s co-offender network and offending versatility. Relying on longitudinal data for a random sample of delinquents from Philadelphia, this study begins by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(87 citation statements)
references
References 59 publications
(72 reference statements)
6
81
0
Order By: Relevance
“…Although the concept of intimate peer groups is a vital component of social learning, McGloin and Piquero (2009), in their study of cooffending, suggest that larger peer groups may be instrumental in crime causation as they provide "situational inducements" through reinforcement of and influence on perceptions of costs and benefits of offending. Their findings indicate a positive association between the size of criminal peer networks and violent behavior.…”
Section: Nonlinearity In Traditional Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the concept of intimate peer groups is a vital component of social learning, McGloin and Piquero (2009), in their study of cooffending, suggest that larger peer groups may be instrumental in crime causation as they provide "situational inducements" through reinforcement of and influence on perceptions of costs and benefits of offending. Their findings indicate a positive association between the size of criminal peer networks and violent behavior.…”
Section: Nonlinearity In Traditional Networkmentioning
confidence: 99%
“…Both peer group size (McGloin & Piquero, 2009) and the proportion of criminal versus non-criminal messages (Haynie, 2002) have a direct influence on personal behavior. Therefore, the number of peers in one's social group plays an instrumental role in the peer influence process; yet is remains unclear whether the same is true of online networks.…”
Section: Introductionmentioning
confidence: 99%
“…The minimal research on co-offending patterns in criminal careers shows that it exhibits a strikingly similar profile to the aggregate age-crime curve van Mastrigt and Farrington 2009), that there are distinct trajectories of co-offending over the course of the juvenile criminal career and that juvenile delinquents generally tend not to ''re-use'' co-offenders, though frequent offenders show a greater propensity to do so (McGloin et al 2008), that higher levels of co-offender network redundancy (more dense networks) are related to higher levels of specialized offending in group crimes, but no such relationship exists with overall (i.e., solo and group) offending diversity (McGloin and Piquero 2009), and that the presence of more co-offenders (i.e., larger groups) will be related to an increased likelihood of violent crime (McGloin and Piquero 2010). However, these studies emerge from two select data sources (the Cambridge data of South London males and a sample of juvenile offenders followed to age 17); thus, there is an important need to examine cooffending patterns in other data sources, across distinct offense types, and throughout the entire life-course.…”
Section: Policy Issuesmentioning
confidence: 99%
“…Although the term itself was coined by Reiss (1980) only 30 years ago, many of the early, 20 th century crime scholars have considered co-offending to one extent or another (e.g., Cloward and Ohlin, 1960;Cohen, 1955;Shaw and McKay, 1942;Shaw and Moore, 1931;Sutherland, 1947). Some studies point to opportunist co-offending patterns (Lantz and Hutchison, 2015;McGloin et al, 2008;Warr, 1996; see also Nagin, Lum, and Solow, 2015), while others have found that crime committed in groups is in fact more profound than solo careerists (McGloin and Piquero, 2010;Felson, 2009). Co-offending groups can vary in size, ranging from three members (Reiss, 1988;Walsh, 1986) to many dozens-as in the case of gangs, "crime-by-association," and organized crime (Klein and Crawford, 1967;Weerman, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is perhaps unsurprising, as human beings are social animals who tend to act in clusters and within various community networks. The type of behavior -criminal or otherwise-undoubtedly shapes the form and size of the group Thomas, 2016a, 2016b; see also Weerman, 2014 andPiquero, 2010), yet there is little disagreement among scholars about the importance of peer influence, interaction rituals, and the existence of social networks, on the likelihood that a specific behavior would take place (Akers, Krohn, Lanza-Kaduce, and Radosevich, 1979;Goffman, 1967). While the interaction between psychological, social, and biological factors are wide and complex, delinquency-much like any other endeavor-is by and large affected by having another person or persons to "do it" with (Morin, 2011; see also Moffitt, 1993).…”
Section: Introductionmentioning
confidence: 99%